Intra-household risk sharing and job search over the business cycle - Haomin Wang (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This paper studies the extent to which working couples can insure one another against cyclical fluctuations in the labor market and examines the implications of joint household decision-making for cyclical fluctuations in the unemployment rate. For this purpose, I provide a dynamic life-cycle model of households that make joint savings and job search decisions in the presence of aggregate shocks. I show that two key mechanisms are at play. The first is the added-worker effect, which leads to counter-cyclical search intensity because workers increase search intensity when their spouse becomes unemployed. The second is the comparative advantage effect, according to which couples' job search efforts are coordinated based on the relative returns to search of each spouse. I estimate the model using data from the US Current Population Survey, and find that joint household decision-making contributes to the counter-cyclicality of women's unemployment rate, but not for men. Moreover, joint household decision-making lowers the welfare costs of cyclicality.
Keywords: J64; E32; D10; 330; Joint Decision-Making; Cyclical Fluctuations; Unemployment Rate; Search Intensity; Intra-Household Risk Sharing